Application Progress of Modified Basalt Fiber Bio-nest Technology in Wastewater Treatment - ZHU Ziyue; LIU Zejun; QI Xiaoyuan; LIU Bingjun; HE Kai; LIANG Zhishui; WU Zhiren (Renmin Zhujiang)
In recent years,Modified basalt fiber (MBF),as a green carrier material for wastewater biological treatment,has drawn much attention.The bio-nest technology based on MBF can not only strengthen the water purification effect but also has the advantages such as low energy consumption and sludge production.The advantages of MBF are demonstrated and compared with common carrier materials in terms of fundamental characteristics,biocompatibility,and other factors.The key points of the MBF bio-nest technology and its water purification mechanism are summarized.On this basis,the application cases of MBF in wastewater treatment are introduced in detail.Furthermore,the future development trend and research priorities for MBF bio-nest technology are forecasted.